Identification of methylation quantitative trait loci (mQTLs) influencing promoter DNA methylation of alcohol dependence risk genes - Zhang, Huiping; Wang, Fan; Kranzler, Henry R.; Yang, Can; Xu, Hongqin; Wang, Zuoheng; Zhao, Hongyu; Gelernter, Joel (Human genetics, 2014)
Interaction of DNA methylation and sequence variants that are methylation quantitative trait loci (mQTLs) may influence susceptibility to diseases such as alcohol dependence (AD). We used genome-wide genotype data from 268 African Americans (AAs: 129 AD cases and 139 controls) and 143 European Americans (EAs: 129 AD cases and 14 controls) to identify mQTLs that were associated with promoter CpGs in 82 AD risk genes. 282 significant mQTL–CpG pairs (9.9 × 10 −100 ≤ P nominal ≤ 7.7 × 10 −8 ) in AAs and 313 significant mQTL–CpG pairs (2.7 × 10 −53 ≤ P nominal ≤ 9.9 × 10 −8 ) in EAs were identified [i.e., mQTL–CpG associations survived multiple-testing correction, q values (false discovery rate) ≤ 0.05]. The most significant mQTL was rs1800759, which was strongly associated with CpG cg12011299 in both AAs ( P nominal = 9.9 × 10 −100 ; q = 6.7 × 10 −91 ) and EAs ( P nominal = 2.7 × 10 −53 ; q = 1.4 × 10 −44 ). Rs1800759 (previously known to be associated to AD) and CpG cg12011299 (distance: 37 bp) are both located in alcohol dehydrogenase (ADH) 4 gene ( ADH4 ) promoter region. In general, the strength of association between mQTLs and CpGs was inversely correlated with the distance between them. Association was also influenced by race and AD. Additionally, 48.3 % of the mQTLs identified in AAs and 65.6 % of the mQTLs identified in EAs were predicted to be expression QTLs. Three mQTLs (rs2173201, rs4147542, and rs4147541 in ADH1B - AHD1C gene cluster region) found in AAs were previously identified by our genome-wide association studies as being significantly associated with AD in AAs. Thus, DNA methylation, which can be influenced by sequence variants and is implicated in gene expression regulation, appears to at least partially underlie the association of genetic variation with AD.